Persistent olfactory dysfunction associated with poor sleep quality and anxiety in patients with long COVID - Paranhos, Alna Carolina Mendes; Dias, Apio Ricardo Nazareth; Bastos, Thalita da Rocha; Rodrigues, Arthur Nascimento; Santana, Karem Harumy Yamamoto; Dias, Lorena Henriete Araujo; dos Santos, Lidiane Palheta Miranda; Cerasi, Antônio José; Mendes, Michely Caroline Nascimento; de Oliveira, Cleiziane Lima; Domingues, Mariângela Moreno; Koury, Gisele Vieira Hennemann; et al. (Frontiers in Neuroscience, 2023)
Introduction Poor sleep quality have been widely reported in patients with long COVID. Determining the characteristics, type, severity, and relationship of long COVID with other neurological symptoms is essential for the prognosis and management of poor sleep quality. Methods This cross-sectional study was conducted at a public university in the eastern Amazon region of Brazil between November 2020 and October 2022. The study involved 288 patients with long COVID with self-report neurological symptoms. One hundred thirty-one patients were evaluated by using standardised protocols: Pittsburgh sleep quality index (PSQI), Beck Anxiety Inventory, Chemosensory Clinical Research Center (CCRC), and Montreal Cognitive Assessment (MoCA). This study aimed to describe the sociodemographic and clinical characteristics of patients with long COVID with poor sleep quality and their relationship with other neurological symptoms (anxiety, cognitive impairment, and olfactory disorder). Results Patients with poor sleep quality were mainly women (76.3%), 44.04 ± 12.73 years old, with >12 years of education (93.1%), and had monthly incomes of up to US $240.00 (54.2%). Anxiety and olfactory disorder were more common in patients with poor sleep quality. Discussion Multivariate analysis shows that the prevalence of poor sleep quality was higher in patients with anxiety, and olfactory disorder is associated with poor sleep quality. In this cohort of patients with long COVID, the prevalence of poor sleep quality was highest in the group tested by PSQI and were associated with other neurological symptoms, such as anxiety and olfactory dysfunction. A previous study indicates a significant association between poor sleep quality and psychological disorders over time. Recent studies involving neuroimaging found functional and structural changes in Long COVID patients with persistent olfactory disfunction. Poor sleep quality are integral part of complex changes related to Long COVID and should be part of patient’s clinical management.